Differential time course of NGF-induced hyperalgesia to heat versus mechanical and electrical stimulation in human skin - Weinkauf, Benjamin; Obreja, Otilia; Schmelz, Martin; Rukwied, Roman (European journal of pain, 2015)
Background: Nerve growth factor (NGF) causes early heat and delayed mechanical hyperalgesia. Axonal transport might contribute to lasting responses. Temporal hyperalgesia development was investigated by administering NGF in paraspinal skin. Transient receptor potential ankyrin 1 (TRPA1) is up-regulated by NGF and chemical responsiveness to cinnamon aldehyde (TRPA1 agonist) was quantified. Methods: Eight healthy volunteers received 1 μg human recombinant NGF (i.d. 50 μL) to L4/L5 processi spinosi skin. Mechanical, thermal and electrical sensitization was assessed at 3-6 h and at days 1, 2, 3, 5, 7, 10, 14 and 21, and pain upon cinnamon aldehyde (20%, 60 μL) recorded at days 3 and 21. Results: Heat hyperalgesia developed with an initial maximum at 3 h [heat pain threshold −3.9°; peak pain ratings +22 visual analogue scale (VAS)] that decreased by day 1, subsequently increased to a maximum around day 5 (−5 ± 0.2 °C, +41 ± 4 VAS), and thereafter declined to ∼20% at day 21. Mechanical and electrical hyperexcitability developed within 3 days and gradually increased to peak between days 14 and 21. Pain intensity upon cinnamon aldehyde stimulation was doubled at the NGF site at day 3 and was still increased by about 50% at day 21. Conclusions: NGF causes immediate heat hyperalgesia probably linked to an up-regulation and sensitization of transient receptor potential vanilloid 1 and possibly other proteins involved in heat transduction. The delayed mechanical hyperalgesia is apparently independent of the time required for axonal transport of NGF receptor complexes. Local mRNA translation at axonal terminals and protein accumulation is hypothesized being involved in sustained NGF-evoked hyperalgesia.
Gesehen am 07.02.2018